Designing Futuristic Telemedicine Using Artificial Intelligence and Robotics in the COVID-19 Era - Bhaskar, Sonu; Bradley, Sian; Sakhamuri, Sateesh; Moguilner, Sebastian; Chattu, Vijay Kumar; Pandya, Shawna; Schroeder, Starr; Ray, Daniel; Banach, Maciej (Frontiers in Public Health, 2020)
Technological innovations such as artificial intelligence and robotics may be of potential use in telemedicine and in building capacity to respond to future pandemics beyond the current COVID-19 era. Our international consortium of interdisciplinary experts in clinical medicine, health policy, and telemedicine have identified gaps in uptake and implementation of telemedicine or telehealth across geographics and medical specialties. This paper discusses various artificial intelligence and robotics-assisted telemedicine or telehealth applications during COVID-19 and presents an alternative artificial intelligence assisted telemedicine framework to accelerate the rapid deployment of telemedicine and improve access to quality and cost-effective healthcare. We postulate that the artificial intelligence assisted telemedicine framework would be indispensable in creating futuristic and resilient health systems that can support communities amidst pandemics.